Estimation of Sea Current Energy Potential by Using Calculation Models of Horizontal Axis Current Turbine in Toyapakeh Strait, Nusa Penida, Bali - Beben Rachmat; Delyuzar Ilahude (Marine Geological Institute of Indonesia, 2017)
Toyapakeh Strait has a fairly strong ocean current velocity with a velocity between 0.5 m/s – 3.2 m/s. The duration of the strong current (V> 0.5 m/s) ranges from 13-22 hours per day. The location of the strong current occurrence is located to the east of Nusa Lembongan Island, precisely at the stationary current measurement location. Vertical distribution of the direction and velocity currents at this location are not uniform from the top to the bottom, especially in the water column depths of 2 m, 4 m and 6 m, whereas at the water column depths of 8 m to 16 m are relatively uniform. Calculation results of potential electrical power by using the horizontal axis turbine model with a capacity of 35.9 kW (Rite Verdan), 100 kW (Tocardo DD702HT) and 250 kW (Tocardo DD1001HT) show that all of the values have the optimal electric powers, especially during the spring tide, whereas during the neap tide only the turbine with a capacity of 35.9 kW can retrieved an optimal electrical power. Calculation result of the electric power potential by using the method of calculation performed by the Electric Power Research Institute Inc. at the point of measurement, indicated that the total amount of energy 42.5 MWh per month for the turbine model Tocardo DD1001HT, 17.27 MWh per month for turbine model DD702HT Tocardo, and 9.08 MWh per month for the turbine model Rite Verdan.Keywords: Toyapakeh Strait, current velocity, time duration, electric power, depth of the water column Perairan Selat Toyapakeh mempunyai kecepatan arus laut yang cukup kuat dengan kecepatan berkisar antara 0,5 m/det – 3,2 m/det. Durasi terjadinya arus kuat (V>0,5 m/det) berkisar 13 – 22 jam per hari. Lokasi tempat terjadinya arus kuat terletak di sebelah timur Pulau Nusa Lembongan, tepatnya di lokasi tempat pengukuran arus stasioner. Secara vertikal distribusi arah dan kecepatan arus di lokasi ini tidak seragam dari atas ke bawah, terutama pada kedalaman kolom air 2 m, 4 m dan 6 m, sedangkan untuk kedalaman kolom air 8 m sampai 16 m relatif seragam. Hasil perhitungan potensi daya listrik dengan menggunakan model turbin sumbu horisontal dengan kapasitas 35,9 kW (Rite Verdan), 100 kW (Tocardo DD702HT) dan 250 kW (Tocardo DD1001HT) diperoleh daya listrik yang cukup optimal terutama saat spring tide, sedangkan saat neap tide hanya turbin dengan kapasitas 35,9 kW yang masih menghasilkan daya listrik secara optimal. Hasil perhitungan potensi daya listrik dengan menggunakan metode perhitungan yang digunakan oleh Electric Power Research Institute Inc. di titik pengukuran diperoleh total energi yang dihasilkan dari model turbin Tocardo DD1001HT adalah sebesar 42,5 MWh per bulan, model turbin Tocardo DD702HT adalah sebesar 17,27 MWh per bulan, dan model turbin Rite Verdan adalah sebesar 9,08 MWh per bulan.Kata Kunci : Selat Toyapakeh, kecepatan arus, durasi waktu, daya listrik, kedalaman kolom air